HEALTHY AND PRODUCTIVE LIFESTYLE EDUCATION FOR YOUTH AT SENIOR HIGH SCHOOL KALAM KUDUS 2 JAKARTA - Ernawati, Ernawati; Yohanes Firmansyah; Alexander Halim Santoso; Sukmawati Tansil Tan; Noer Saelan Tadjudin; Sari Mariyati Dewi Nataprawira; Susy Olivia Lontoh; Hendsun, Hendsun; Fendy Wellen; Jeffry Luwito; Valeria Saputra; Stanley Surya Cahyadi; Muhamad Rizki Nanda F (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Clean and Healthy Living Behavior is an endeavor to live a healthy lifestyle at both the individual and communal levels. In the current pandemic era, it is crucial to focus on Clean and Healthy Living Behavior in order to avoid various viruses and diseases. The necessity of Clean and Healthy Behavior must continue to be emphasized to all segments of society. Youth is a group that need attention. According to a situational analysis conducted at SMA Kalam Kudus II in Jakarta, there is a problem with poor levels of cleanliness and health consciousness. To raise high school students' understanding of clean and healthy lives, it is required to conduct activities such as lectures, discussions, and outreach. This service activity takes place in Kalam Kudus II Jakarta High School. This service action was accomplished by performing a survey of service sites, preparing service locations, and delivering Clean and Healthy Behavior support resources. Youth members have participated in Clean and Healthy Living Behavior socialization activities using lecture, discussion, and question and answer formats. This service activity worked smoothly overall. The conclusion that can be derived from this is that service activity participants recognize the significance of clean and healthy lifestyle choices in preventing various diseases.